Growth and Development of a Malaysian Dipterocarp Forest After Harvest - Karkee, Thakur Babu (1993)
The success of the Selective Management System (SMS) in managing" the hill dipterocarp forests of Peninsular Malaysia depends, among others, on the types of trees in the residual stand and the ability of these trees to grow and form the next crop. Specific information on growth and development of the residual stand is urgently required to evaluate the management system and its suitability in different forest types. In this study, data are analysed from logged over stands in the Lebir Forest Reserve, Peninsular Malaysia, which has been subjected to three harvesting intensities (HIs). The data consists of nine measurements covering a 14-year (1978-1991) period collected from nine permanent sample plots of size 200X200 m design under the systematic line sampling method. The plots were harvested first in 1977. Stocking, basal area and dbh growth of most species groups and HIs trees over 5 cm and over 15 cm dbh after harvest were significantly different (p<0.01) between the hill and lowland forests. The 5-15 cm dbh trees constituted more than 70 % of the total stocking and 20 % of total basal area. The stocking by dbh classes followed an inverse J-shape curve. The residual stand was dominated by non-dipterocarps. The potentially marketable (PM) and non-marketable species together accounted for more than 60% of total stocking and 58 % of total basal area in the both forests.